LncRNA small nucleolar RNA host gene 1 (SNHG1) mediates acidic bile salt-induced EMT via the ULK1-Notch1 axis in Barrett’s esophagus - Jianfeng Zhou; Rongyan Zhao; Zixiang Li; Xuelan Ma; Wenke Jin; Yong Yuan; Ning Li; Bo Liu; Yushang Yang (Molecular Biomedicine)
Abstract Barrett’s esophagus (BE) is a precancerous condition closely linked to chronic gastroesophageal reflux disease, characterized by the abnormal transformation of esophageal squamous mucosa into specialized intestinal-type epithelium, significantly elevating the risk of esophageal adenocarcinoma (EAC). Recurrent acidic bile reflux promotes epithelial-mesenchymal transition (EMT), a critical event driving malignant progression. However, the underlying molecular mechanisms remain incompletely understood. Here, we identify the long non-coding RNA small nucleolar RNA host gene 1 (SNHG1) as a novel regulator of EMT in BE, mediating its effects through the UNC-52-like kinase 1 (ULK1)-Notch1 signaling axis and autophagy modulation. Using BAR-T and CP-C cell models, we demonstrate that SNHG1 expression is elevated following acidic bile salt exposure, enhancing EMT characteristics by promoting the phosphorylation of ULK1 and activating Notch1 signaling. Pharmacological interventions targeting autophagy (Rapamycin) and Notch signaling (DAPT) further confirmed that SNHG1’s effects on EMT are mediated via modulation of the autophagy-Notch1 interplay. We further validated our results in vivo using the previously described IL1β-induced Lgr5-CreERT2; p16flox/flox/KrasG12D mouse model, which reliably reproduces the histological progression of Barrett’s-like dysplasia in the squamocolumnar junction (SCJ), confirming SNHG1’s critical role in regulating EMT and BE progression. Additionally, SNHG1 expression was significantly elevated in patients who progressed to low- or high-grade dysplasia, as confirmed by diagnostic endoscopic biopsies. Collectively, our study uncovers SNHG1 as a central molecular mediator linking acidic bile-induced EMT and autophagy regulation via the ULK1-Notch1 axis, highlighting its potential as a therapeutic target for preventing BE recurrence and progression to EAC.